Retention in Plaque and Remineralization of Enamel Lesions by Various Forms of Calcium in a Mouthrinse or Sugar-free Chewing Gum - Reynolds, E.C.; Cai, F.; Shen, P.; Walker, G.D. (Journal of dental research, 2003)
Casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) nanocomplexes incorporated into sugar-free chewing gum have been shown to remineralize enamel subsurface lesions in situ. The aim of this study was to compare the ability of CPP-ACP, with that of other forms of calcium, to be retained in supragingival plaque and remineralize enamel subsurface lesions in situ when delivered in a mouthrinse or sugar-free gum in randomized, double-blind trials. In the mouthrinse study, only the CPP-ACP-containing mouthrinse significantly increased plaque calcium and inorganic phosphate levels, and the CPP were immunolocalized to the surfaces of bacterial cells as well as the intercellular matrix. In the chewing gum studies, the gum containing the CPP-ACP, although not containing the most calcium per piece of gum, produced the highest level of enamel remineralization independent of gum-chewing frequency and duration. The CPP could be detected in plaque extracts 3 hrs after subjects chewed the CPP-ACP-containing gum. The results showed that CPP-ACP were superior to other forms of calcium in remineralizing enamel subsurface lesions.